O ato empático na constituição da pessoa humana : repensando a questão da empatia a partir de Edith Stein - Amaral, Antonio de Souza (2023)
This research is meant to work on the theme of empathy according to the vision of the German philosopher Edith Theresa Hedwing Stein (1891-1942). It begins with the understanding of the phenomenological method, through a rigorous analysis of the studies developed by the author – in particular “On the problem of empathy” – seeking to find the fundamental elements of the issue of empathy, and, successively, to elucidate and present how it is constituted and developed the empathic act in the formative process of the human person. In the face of a bibliographical research, we propose: to analyze the objective method of essences, to seek to understand the constitution of acts experienced with empathy, as well as the empathic acts that direct us to moral values and, finally, to present empathy as a fundamental skill for the living and social dimension in the constitution of the human being. The analyzes carried out reveal that Edith Stein proposes the concept of empathy as a means to understand the human experience and as a means to help people connect in their relationships. Stein's concept of empathy is based on the theory of phenomenology. She believes that when two people come into contact with each other, they become aware of the other as someone who is unique and distinct. This awareness is called “empathy”. Stein also argues that empathy is a necessary means for people to achieve true mutual understanding and compassion. Empathy allows people to better understand what the other is feeling. It's a way of putting yourself in the other person's shoes, which is necessary to build meaningful relationships.